2022
DOI: 10.1007/s40888-021-00255-3
|View full text |Cite
|
Sign up to set email alerts
|

Does social capital enforce social distancing? The role of bridging and bonding social capital in the evolution of the pandemic

Abstract: By shaping the way people look at members of their networks as well as strangers, social capital affects the behavior of a population during a pandemic. Over the course of 2020, various countries implemented non-pharmaceutical interventions (NPI), imposing restrictions that were difficult to enforce (due to the scale of the policies) in order to protect the public from the threat of COVID-19. This is an interesting quasi-experimental setting in which to test the compliance of populations with different levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 69 publications
2
30
0
1
Order By: Relevance
“…It has been recognized that the discrepancy in responses to public health interventions across various communities in the US and elsewhere is due to different patterns of social interaction. Nowhere was the importance of understanding and measuring social capital more noticeable than during the recent COVID-19 pandemic (Alfano, 2022 ; Wong & Kohler, 2020 ). Different regional distributions of social capital and rates of urbanization clearly accounted for variations in vaccination uptake across many countries (Qiao et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been recognized that the discrepancy in responses to public health interventions across various communities in the US and elsewhere is due to different patterns of social interaction. Nowhere was the importance of understanding and measuring social capital more noticeable than during the recent COVID-19 pandemic (Alfano, 2022 ; Wong & Kohler, 2020 ). Different regional distributions of social capital and rates of urbanization clearly accounted for variations in vaccination uptake across many countries (Qiao et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…This happens because, without cures or vaccines, the only ways to halt the spread of contagion are social distancing and other NPIs. Another common assumption in this literature ( Alfano and Ercolano, 2021a , b ; Alfano, 2021 ; 2022 ) is to consider NPIs as policies whose effectiveness depends principally on voluntary compliance among the population, given how complex it would be for a government to enforce them through the use of public force. Hence, when comparing country-level COVID-19 diffusion rates among different countries, controlling for the different levels of NPI stringency is considered a good measure of the levels of compliance with these policies among the population (Alfano and Ercolano, 2021a ; Alfano, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…This limit has been overcome by previous studies ( Alfano and Ercolano, 2021a , b ) by dividing the sample by quantiles of the variable of interest and estimating the impact in different subsamples, for later comparison among the betas. It has been noted that this empirical strategy has two main limitations ( Alfano, 2021 ; 2022 ): first, comparing betas that have been estimated in different samples may lead to inconsistent conclusions, since these could be subsamples affected by different biases and errors; second, dividing the sample by quantiles of one variable also implies dividing it by all the variables that are highly correlated with it, creating uncertainty in the identification of the effect, which could be due to some omitted variable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, as prior research has shown, food insecurity is a potent stressor with deleterious consequences particularly for the old, or more ‘vulnerable,’ population [ 14 , 15 , 16 , 17 ]. On the other, empirical evidence points to health advantages of ecological or contextual social capital, i.e., community-level resources such as norms of reciprocity, collective identity, and mutual support [ 18 , 19 , 20 , 21 , 22 , 23 ]. We build on this line of research by conceptualizing community social capital as a collective resource in buffering the negative effect of social distancing.…”
Section: Introductionmentioning
confidence: 99%